2011
DOI: 10.1186/1471-2334-11-344
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis temporally associated with live attenuated Japanese encephalitis vaccine: four case reports

Abstract: BackgroundJapanese encephalitis (JE) vaccination is the most effective measure for preventing JE disease. The live attenuated JE vaccine, which has shown good efficacy and safety, has been widely used in China.Case presentationsWe report four laboratory-confirmed JE cases detected in JE-endemic areas during the JE virus (JEV) transmission season, who all received a first dose of live attenuated JE vaccine within 2 weeks prior to the onset of illness. All cases presented with acute encephalitis and rapidly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In a prospective, randomized study where patients were actively monitored for 30 days, no cases of encephalitis or meningitis were observed, and no differences in hospitalization or prolonged fever were found ( 10 ). However, recent encephalitis cases have been reported in Chinese patients who received a first dose of LAJEV, although it is difficult to identify the causal link between the disease and JE vaccination ( 27 ). Therefore, concerns about safety still remain, and continued surveillance and careful investigation of any events that occur after LAJEV is required.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, randomized study where patients were actively monitored for 30 days, no cases of encephalitis or meningitis were observed, and no differences in hospitalization or prolonged fever were found ( 10 ). However, recent encephalitis cases have been reported in Chinese patients who received a first dose of LAJEV, although it is difficult to identify the causal link between the disease and JE vaccination ( 27 ). Therefore, concerns about safety still remain, and continued surveillance and careful investigation of any events that occur after LAJEV is required.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were apparently healthy and did not complain of any ailment at the time of enrolment in the study. Previous studies have reported two deaths and encephalitis case following the administration of LAJEV but were non-conclusive and judged as unrelated to the vaccine2627. Therefore, vigilant surveillance and complete investigations of any event following vaccination should be emphasized.…”
Section: Discussionmentioning
confidence: 98%
“…The occurrence of seizures can be mediated by the immune system [13]. JEV is a vaccine that can cause a wide variety of complications, including encephalitis [11,14,15]. Seizures secondary to JEV have, however, not been reported to date.…”
Section: Discussionmentioning
confidence: 99%